Film credits: representations of power, artistic and creative influence - Coelho, Inês Rebanda (2020)
When watching a cinematographic work, the credits are frequently one of the elements that go mostly unnoticed in the eyes of its viewers, and, even when this does not happen, there is a tendency to just observe the names of those who performed a specific job in that work. However, there are several meanings and subliminal messages that can be found in the title sequences, especially in the opening credits. In this sense, a study was carried out aiming at the figure of the cinema producer. Twelve American and European producers were selected and studied. The initial credits of their works were thoroughly analyzed, as well as other films randomly selected. In total, 384 films were examined. After this analysis, a categorization expressed in mathematical language was created and divided into two main categories: financial producer and creative producer. Through this study, it was possible to catalog three types of special credits, which were called declarative credits, possessive credits (or possessory credits) and declarative/possessive credits. It was also possible to extract from these credits the most diverse messages regarding the creative and artistic acts of several producers, as well as their influence and power in the creation of the cinematographic works in question. This article intends to report all the new knowledge that was possible to acquire through the complete observation of the film credits mentioned above.